2021
DOI: 10.1038/s41598-021-03214-x
|View full text |Cite
|
Sign up to set email alerts
|

Common osteoporosis drug associated with increased rates of depression and anxiety

Abstract: Osteoporosis affects over 10 million Americans over 50. Bisphosphonate therapy, mainly alendronate, is amongst the most prescribed treatments for the disease. The use of alendronate and other bisphosphonates has been associated with depressive symptoms in recent case reports. In this study we quantified this association by analyzing over 100,000 adverse events reports from the Food and Drug Administration Adverse Events Reporting System (FAERS) and the World Health Organization’s (WHO) global database for adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Currently, various pharmacological therapies are clinically used for the treatment of osteoporosis including bisphosphonates, teriparatide, denosumab, and romosozumab; however, various health concerns have been raised with their long-term administration. A study reported that the most prescribed osteoporosis drugs such as bisphosphonates and alendronate are found to be associated with the enhanced rate of developing depression and anxiety along with other adverse side effects ( 19 ). Thus, there is an exigent need to identify and develop safer therapies with minimal or no side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various pharmacological therapies are clinically used for the treatment of osteoporosis including bisphosphonates, teriparatide, denosumab, and romosozumab; however, various health concerns have been raised with their long-term administration. A study reported that the most prescribed osteoporosis drugs such as bisphosphonates and alendronate are found to be associated with the enhanced rate of developing depression and anxiety along with other adverse side effects ( 19 ). Thus, there is an exigent need to identify and develop safer therapies with minimal or no side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Anabolic agents are capable of restoring the BMD, filling in the bone remodeling space, actively raising the bone mass, and decreasing the consequences of osteoporotic fractures [ 5 ]. Moreover, resorption inhibitors such as alendronate and other bisphosphonates have been linked to a greater prevalence of depressive symptoms in recent case reports [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changing lifestyle habits requires extensive and in-depth health education and a high degree of patient compliance. Currently, bisphosphonates are widely used in the clinical treatment of osteoporosis, but the side effects, such as abdominal pain, kidney disease, and cardiovascular disease, cannot be ignored [ 12 15 ]. In addition, romosozumab, teriparatide, denosumab, and SERM are also used to treat osteoporosis.…”
Section: Introductionmentioning
confidence: 99%